Festuca carpetana (Poaceae), a new species for the Iberian flora - de la Fuente, Vicenta; Sánchez-Mata, Daniel (Lazaroa, 2014)
A new species is proposed for the Iberian Peninsula flora: Festuca carpetana. A brief discussion and justification arepresented, along with the main differences between Festuca indigesta Boiss. and the new proposed species, including twooriginal plates from SEM samples.